The Effectiveness of Termination of Prosecution in Settling Theft Crimes Based on Restorative Justice - Tony Aji Kurniawan; Andi Winjaya Laksana (UNISSULA Semarang, 2025)
This study aims to determine and analyze the implementation of termination of prosecution in criminal acts of theft based on restorative justice, the weaknesses of termination of prosecution in criminal acts of theft based on restorative justice and the effectiveness of termination of prosecution in criminal acts of theft based on restorative justice. The method of this research approach is sociological juridical, the research specification is analytical descriptive. The data used are primary data and secondary data and the data collection method is field study and literature study, while the data analysis method uses qualitative analysis. The theories used are restorative justice theory, legal effectiveness theory and progressive legal theory. Based on the results of the study, it can be concluded that the implementation of termination of prosecution in criminal acts of theft based on restorative justice at the Pekalongan Regency District Attorney's Office has been carried out in accordance with Perja Number 15 of 2020, namely fulfilling formal and material requirements and procedures according to the provisions. Weaknesses of the termination of prosecution in the crime of theft based on restorative justice include the lack of explicit regulation of restorative justice in the law (KUHAP), termination of prosecution based on restorative justice depends on the willingness of all parties, the need for trained and professional facilitator prosecutors, limited number of prosecutors and time constraints, the potential for injustice to victims, ignoring the deterrent effect for perpetrators, and weak oversight of peace agreements. These weaknesses can hinder the achievement of the goals of restorative justice. The termination of prosecution in the crime of theft based on restorative justice has not been fully effective, considering that many cases planned to be resolved based on restorative justice failed. However, cases that have been resolved based on restorative justice have been effective.